2014
DOI: 10.1108/rpj-11-2012-0098
|View full text |Cite
|
Sign up to set email alerts
|

Development of acrylate-based material using a multivariable approach: additive manufacturing applications

Abstract: Purpose -Over the last several years, the range of applications for the photopolymerisation process has been steadily increasing, especially in such areas as rapid prototyping, UV inks, UV coats and orthodontic applications. In spite of this increase, there are still several challenges to be overcome when the application concerns materials formulation and their mechanical properties. In this context, the main aim of this work is to outline the contribution of the formulation components for the parameters of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…8), Cunico and Carvalho found that photoinitiator (PI) concentration had a tremendous effect on both modulus and tensile strength. 154 Thus polymers cured for 20 minutes with 5 wt% PI (Omnirad 2500 from IGM) were on average 40% stiffer and half as strong as those cured with 2 wt% PI. Interestingly DBC for the polymer with 2 wt% PI was 90% after 60 seconds while the value was only 65% for the same polymer with 5 wt% PI.…”
Section: Considerations For Radical Chain Growthmentioning
confidence: 98%
“…8), Cunico and Carvalho found that photoinitiator (PI) concentration had a tremendous effect on both modulus and tensile strength. 154 Thus polymers cured for 20 minutes with 5 wt% PI (Omnirad 2500 from IGM) were on average 40% stiffer and half as strong as those cured with 2 wt% PI. Interestingly DBC for the polymer with 2 wt% PI was 90% after 60 seconds while the value was only 65% for the same polymer with 5 wt% PI.…”
Section: Considerations For Radical Chain Growthmentioning
confidence: 98%
“…Photopolymerization is the critical mechanism of SLA 3D printing technology, demonstrating superior performance in the manufacture of 3D objects with accuracy, rapid curing, and micro-nanoscale resolution [9][10][11]. Nowadays, the photopolymerization applications and their utilization among industries are striking as well as modest schemes involving polymer chemistry [12]. The working principle of SLA techniques has made it more conceivable to decrease the cost of the manufacturing processes with high-quality products [13].…”
Section: Introductionmentioning
confidence: 99%